PENGUATAN KAPASITAS BADAN USAHA MILIK DESA MOIN FE'U MELALUI PELATIHAN LITERASI FINANSIAL DI DESA FATUKANUTU KECAMATAN AMABI OEFETO - Herry Aprilia Manubulu; Renya Rosari (Bakti Cendana, 2022)
The existence of the Moin FE’U Bumdes has the aim of supporting the improvement of the welfare of the Fatukanutu village community and the Moin FE'U BUMDES can develop business units in utilizing the village's economic potential. Seeing the importance of the existence of BUMDES Moin Fe’U in an effort to improve the welfare of rural communities, the urgency of the need for service for BUMDES Moin FE'U is training to strengthen the capacity of village-owned enterprises through financial literacy training. Participants in this service are village officials and managers of BUMDES Moin Fe'U. The method of implementing the service is lecture, discussions and training. The stages implementation are 1) delivery of material about bussines plan and financial reports, 2) discussions, 3) the practice of preparing financial reports. The result of this PKM is for village officials and managers of Bumdes Moin Fe'U can make a bussines plan proposal and able to compile financial reports based on SAK ETAP.